Comparative Genomic Analysis of Rhodococcus equi: An Insight into Genomic Diversity and Genome Evolution. (20th December 2019) - Ying, Jianchao; Ye, Jun; Xu, Teng; Wang, Qian; Bao, Qiyu; Li, Aifang
Abstract : Rhodococcus equi, a member of the Rhodococcus genus, is a gram-positive pathogenic bacterium. Rhodococcus possesses an open pan-genome that constitutes the basis of its high genomic diversity and allows for adaptation to specific niche conditions and the changing host environments. Our analysis further showed that the core genome of R. equi contributes to the pathogenicity and niche adaptation of R. equi . Comparative genomic analysis revealed that the genomes of R. equi shared identical collinearity relationship, and heterogeneity was mainly acquired by means of genomic islands and prophages. Moreover, genomic islands in R. equi were always involved in virulence, resistance, or niche adaptation and possibly working with prophages to cause the majority of genome expansion. These findings provide an insight into the genomic diversity, evolution, and structural variation of R. equi and a valuable resource for functional genomic studies.